Energy, Resource Extraction and Society
1 online resource (236 pages)
Keywords: Energy is central to the fabric of society. This book revisits the classic notions of energy impacts by examining the social effects of resource extraction and energy projects which are often overlooked. Energy impacts are often reduced to the narrow configurations of greenhouse gas emissions, chemical spills or land use changes. However, this neglects the fact that the way we produce, distribute and consume energy shapes society, political institutions and culture. The authors trace the impacts of contemporary energy and resource extraction developments and explain their significance for the shaping of powerful social imaginaries and a reconfiguration of political and democratic systems. They analyse not only the complex histories and landscapes of industrial mining and energy development, including oil, coal, wind power, gas (fracking) and electrification, but also their significance for contested energy and social futures. Based on ethnographic and interdisciplinary research from around the world, including case studies from Australia, Germany, Kenya, the Netherlands, Nicaragua, Norway, Poland, Turkey, UK and USA, they document the effects on local communities and how these are often transformed into citizen engagement, protest and resistance. This sheds new light on the relationship between energy and power, reflecting a wide array of pertinent impacts beyond the usual considerations of economic efficiency and energy security. The volume is aimed at advanced students and researchers in anthropology, sociology, human geography, science and technology studies, environmental studies and sustainable development as well as professionals working in the field of impact assessments.